Outdoor gyms as an example of outdoor recreation activity in urbanized areas - Nałęcz, Hanna; Ostrowska-Tryzno, Anna; Pawlikowska-Piechotka, Anna (Turyzm/Tourism, 2018)
In recent years, the popularity of outdoor gyms has been growing. They are built in urban parks, in neighbourhoods (housing estates), at school sports grounds. Recently more and more outdoor gyms are increasingly being built also in non-urban recreation areas (such as coastal beaches, lake promenades, forest parks). The aim of this research was to analyse how outdoor gyms in Warsaw and the selected surrounding localities are used.